Ejemplo de un tratamiento documental en la enseñanza de la literatura. Poemas seleccionados de Antonio Machado - Gamarra González, M.ª Isabel (Revista General de Información y Documentación, 2003)
After setting out the theoretical basis, an example using some of the poems of Machado is given of documentary treatment for application in the teaching of Literature. The method used is that of content analysis and the stages of the process are: bibliographical description, thematic profiles record, and synthetic-analytical gloss of each poem and, finally, its evaluation.